2012
DOI: 10.1007/s11422-012-9396-0
|View full text |Cite
|
Sign up to set email alerts
|

How can video supported reflection enhance teachers’ professional development?

Abstract: This paper responds to Eva Lundqvist, Jonas Almqvist and Leif Ostman's account of how the manner of teaching can strongly influence pupil learning by recommending video supported reflection as a means by which teachers can transform the nature of their practice. Given the complex nature of the many conditions which influence and control teachers' actions the reframing of routine practice through reflection-in-action can prove challenging. This response paper describes how video can empower teachers to take gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…Lastly, it is recommended that teachers be provided opportunities to reflect on their classroom teaching practices. Several of the studies in this meta‐analysis indicated the ability of online PD to facilitate the process of teachers reflecting on their own practice and the practices of their colleagues (Berger et al., ; Fry, ; McAleer & Bangert, ; McCullagh, ; Oner & Adadan, ; Powers et al., ; West et al., ). School policies that set aside time during the traditional school day for teachers to access online environments and tools that allow them to view and reflect on uploaded videos of their teaching practice and the practice of their colleagues are needed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lastly, it is recommended that teachers be provided opportunities to reflect on their classroom teaching practices. Several of the studies in this meta‐analysis indicated the ability of online PD to facilitate the process of teachers reflecting on their own practice and the practices of their colleagues (Berger et al., ; Fry, ; McAleer & Bangert, ; McCullagh, ; Oner & Adadan, ; Powers et al., ; West et al., ). School policies that set aside time during the traditional school day for teachers to access online environments and tools that allow them to view and reflect on uploaded videos of their teaching practice and the practice of their colleagues are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple research studies have indicated the ability of online teacher PD to facilitate active learning. Collectively, the results of these studies demonstrated that online PD enabled teachers to actively learn by (a) reflecting on their student's work, (b) reflecting on their own classroom practices, (c) receiving feedback on their work from their peers, and (d) engaging with their peers in online discussion forums (Berger et al., ; Carr, ; Hutchison & Colwell, ; Maxwell et al., ; McAleer & Bangert, ; McCullagh, ; Oner & Adadan, ; Powers et al., ; Russell et al., ; West et al., ).…”
Section: Critical Features Of Pdmentioning
confidence: 97%
See 2 more Smart Citations
“…Teachers cannot pay equal attention to all classroom events and in fact only focus on their favorable events while critical events are overlooked either from teachers' sight or memory whereas these critical incidents are the keywords for precise classroom practices improvement [5]. Video technology is said to be an effective medium to aid teachers to see what is happening in their classrooms as to ensure they could modify the classroom practice effectively [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%